Interregional Trade of High-value Fruits and Vegetables: Issues on Transport and Shipping - Gilberto M. Llanto; Francis Mark A. Quimba; Mercedita A. Sombilla (Philippine Institute for Development Studies (PIDS), 2012)
The study focuses on the transport of vegetable and fruit produce from Mindanao, a major food producing area, to particular regions in Luzon and Visayas to meet increasing market demands. The estimated gravity model showed the key determinants of interregional trade. Economic growth in both sending and recipient regions is necessary for interregional trade to flourish. Economic growth and interregional trade are anchored on access to markets by various economic agents, which is facilitated by the presence of hard and soft infrastructure that make interregional exchange possible.Because distance drives up transport and marketing costs, the necessity of a good network of roads and ports that links production areas to consumer markets cannot be underestimated. The lack of an efficient transport and distribution system increases the cost of transporting agricultural produce, reduces the quality and quantity of those goods, and diminishes the profitability of actors involved in the supply chain. Inadequacy of infrastructure has been a major reason for the country's lack of competitiveness and attraction as a viable and profitable business destination.There is a scope for government intervention at two levels. At the macro level, government has a critical role to play in increasing investments in roads and ports, portside facilities, and related investments; in improving monitoring and coordination of markets; and in ensuring effective regulation at the national and local level.
Keywords: 330; interregional trade; Philippines; supply chain; logistics; transport; gravity model; shipping; Gemüse; Obst; Interregionaler Handel; Wertschöpfung; Gravitationsmodell; Philippinen